SCIENTIFIC AND PRACTICAL APPROACHES TO LEGISLATIVE SUPPORT OF SERVICE AND COMBAT ACTIVITIES OF THE NATIONAL GUARD OF UKRAINE - Balan, M.; Kryvenko, O. (Honor and Law, 2020)
The article outlines the basic principles and conceptual views on improving the legislative support of service and combat activities of the National Ukraine. The National Guard of Ukraine is an effective subject of counteracting the threats to independence, territorial integrity and internal stability during the hybrid war against Ukraine. Given the strategic course of the state towards Ukraine's full membership in the European Union and the North Atlantic Treaty Organization, the issue of bringing the functions of the National Guard of Ukraine closer to the standards of the European Union becomes relevant. Rapid changes in the security environment around and within Ukraine, the emergence of new threats require a timely response. The legal basis for taking measures is to improve the legislation, including by amending the Code of Ukraine on Administrative Offenses, the Law of Ukraine “On the National Guard of Ukraineˮ, etc. The authors emphasize that the National Guard of Ukraine has currently implemented a significant range of reforms aimed at enhancing the capabilities of units and subdivisions, professionalization of personnel, and approximation to the requirements of NATO standards (for military functions) and FIEP standards (for law enforcement functions). The issues of improving the legislative support of the National Guard of Ukraine are currently relevant and need further development.